LGG-34. CLINICAL AND MOLECULAR CHARACTERIZATION OF A MULTI-INSTITUTIONAL COHORT OF PEDIATRIC SPINAL CORD LOW-GRADE GLIOMAS. (4th December 2020) - Grob, Sydney; Nobre, Lianna; Davies, Kurtis; Ryall, Scott; Aisner, Dara; Hoffman, Lindsey; Zahedi, Shadi; Morin, Andrew; Nellan, Anandani; Green, Adam; Foreman, Nicholas; Vibhakar, Rajeev; et al.
Abstract: BACKGROUND: The MAPK/ERK pathway is involved in cell growth and proliferation, and mutations in the BRAF paralog of this pathway have made it an oncogene of interest in pediatric cancer. Previous studies have identified that BRAF mutations as well as BRAF-KIAA1549 fusions are common in intracranial low-grade gliomas (LGGs). Fewer studies have tested for the presence of these genetic aberrations in spinal LGGs. The aim of this study was to better understand the prevalence of BRAF and other genetic aberrations in spinal LGG. METHODS: We analyzed 46 spinal LGGs from children age 1–25 years from two institutions, Children's Hospital Colorado (CHCO) and The Hospital for Sick Children (Sick Kids) for the presence of BRAF fusions or mutations. Data was correlated with clinical information. A 67 gene panel additionally screened for other possible genetic abnormalities of interest in the patient cohort from CHCO. In the Sick Kids cohort, BRAF V600E was tested for by ddPCR and IHC while BRAF fusions where detected by FISH, RT-PCR or Nanostring platform. RESULTS: Of the 31 patient samples who underwent fusion analysis, 13 (42%) harbored the BRAF-KIAA1549 fusion. Overall survival (OS) for patients confirmed positive for BRAF-KIAA1549 was 100% compared to 76% for fusion negative patients. Other mutations of interest were also identified in this patient cohort including BRAF V600E, STK11, PTPN11, H3F3A, APC, TP53, PIK3CA (polymorphism), FGFR1, and CDKN2A deletion. CONCLUSION: BRAF-KIAA1549 was seen in higher frequency than BRAF V600E or other genetic aberrations in pediatric spinal LGGs and trends towards longer OS although not statistically significant.